Versatile Activities of Pyrazoles: Mini Review - Siddiqui, Nadeem; Nusrat, Birjees; Ahsan, Waquar (Asian Journal of Pharmaceutical Research and Development, 2013)
Pyrazoles and their derivatives are an important class of five member nitrogen containing hetrocyclic compounds having much importance on account of their biological activities.These compounds have shown much attention recently due to their diverse biological profile.The importance of the pyrazole nucleus in the field of medicinal chemistry has given a great impetus to search for new potential drugs.